Radiation-induced vulvar angiokeratoma along with other late radiation toxicities after carcinoma cervix: A rare case report - Virendra Bhandari; Ayush Naik; K L Gupta; Mehlam Kausar (Wolters Kluwer Medknow Publications, 2016)
Angiokeratoma including vulvar angiokeratoma is a very rare complication of radiation. Exact incidence is still unknown, we report a case that developed radiation-induced angiokeratoma of skin in the vulvar region along with other late radiation sequelae in the form of bone fracture, new bone formation, bone marrow widening, muscle hypertrophy, and subcutaneous fibrosis, 18 years after radiotherapy to the pelvic region for the treatment of carcinoma cervix. All these late radiation sequel are rare to be seen in a single patient, and none of the case reports could be found in the world literature.